Association of bronchial hyperresponsiveness and lung function with C-reactive protein (CRP): a population based study. Issue 10 (28th September 2004) - Kony, S; Zureik, M; Driss, F; Neukirch, C; Leynaert, B; Neukirch, F
Abstract : Background: C-reactive protein (CRP), a marker of systemic inflammation, is a powerful predictor of adverse cardiovascular events. Respiratory impairment is also associated with cardiovascular risk. Although some studies have found an inverse relationship between lung function and markers of systemic inflammation, only one study has reported a relationship between lung function and CRP levels. In contrast, little is known about the relationship between bronchial hyperresponsiveness (BHR) and systemic inflammation. The association between lung function and CRP and between BHR and CRP has been investigated. Methods: As part of the European Community Respiratory Health Survey follow up study serum CRP levels, forced expiratory volume in 1 second (FEV1 ), and BHR to methacholine (⩾20% decrease in FEV1 to <4 mg methacholine) were measured in 259 adults aged 28–56 years free of cardiovascular disease or respiratory infection. Results: Mean (SD) FEV1 (adjusted for age, sex, height, and smoking status) was lower in subjects with a high CRP level (high tertile) (3.29 (0.44) l/s v 3.50 (0.44) l/s; p<0.001) and BHR was more frequent (41.9% v 24.9%; p = 0.005) than in subjects with lower CRP levels (low+middle tertiles). Similar results were obtained when the potential confounding factors were taken into account. Similar patterns of results were found in non-smokers and in non-asthmatic subjects. Conclusions: Increased CRP levels are strongly and independently associated with respiratory impairment and more frequent BHR. These results suggest that both respiratory impairment and BHR are associated with a systemic inflammatory process.